Antibacterial Potentiality of Ethanol and Ethyl Acetate Extract of Acalypha indica against Human Pathogenic Bacteria - Sathiyaseelan; Sajani Samuel, P. Saranraj*, D. Stella, K. (Journal of Ecobiotechnology, 2010)
Abstract <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;"><span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Medicinal plants have been used as a source of medicine and in widespread use of herbal remedies and healthcare preparations. Nowadays, several plants have been identified for their antimicrobial properties. The present study was conducted to evaluate the antibacterial potentiality of ethanol and ethyl acetate solvent extracts of mature leaves of Acalypha indica against nine pathogenic bacterial isolates viz., Staphylococcus aureus, Bacillus subtilis, Bacillus cereus, Escherichia coli, Salmonella typhi, Shigella flexneri, Klebsiella pneumoniae, Vibrio cholerae and Pseudomonas aeruginosa. The turbidity of the bacterial inoculums was compared with 0.5 Mc Farland standards and the antibacterial potential of Acalypha indica ethanol extract was tested by using Agar well diffusion method. The ethanol extract of Acalypha indica (100 mg/ml) showed maximum zone of inhibition (30 mm) against Pseudomonas aeruginosa, Escherichia coli and Bacillus subtilis. Staphylococcus aureus showed less zone of inhibition (12 mm). The ethyl acetate extract of Acalypha indica (100 mg/ml) showed maximum zone of inhibition (23 mm) against Escherichia coli. There was no zone of inhibition against Pseudomonas aeruginosa. Phytochemical tests were performed and showed that the antibacterial activity of Acalypha indica plant leaves was due to the presence of phytochemical compounds like alkaloids and tannins.